2012
DOI: 10.1200/jop.2012.000548
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Stereotactic Body Radiation Therapy Versus Intensity-Modulated Radiation Therapy: An Emerging Initial Radiation Treatment Option for Organ-Confined Prostate Cancer

Abstract: Purpose: The purpose of this study is to compare the costeffectiveness of two external beam radiation therapy techniques for treatment of low-to intermediate-risk prostate cancer: stereotactic body radiation therapy (SBRT) and intensity-modulated radiation therapy (IMRT). Materials and Methods:A Markov decision analysis model with probabilistic sensitivity analysis was designed with the various disease states of a 70-year-old patient with organ-confined prostate cancer to evaluate the cost-effectiveness of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 37 publications
1
76
0
Order By: Relevance
“…Findings from studies on efficacy and toxicity are summarised in Tables I and II. Treatment cost effectiveness. Two studies were identified that compared estimated mean costs of SBRT and CF-EBRT for early-stage prostate cancer (33,34). Results from both studies support the hypothesis that SBRT is associated with a smaller economic burden for patients and departments compared to CF-EBRT.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Findings from studies on efficacy and toxicity are summarised in Tables I and II. Treatment cost effectiveness. Two studies were identified that compared estimated mean costs of SBRT and CF-EBRT for early-stage prostate cancer (33,34). Results from both studies support the hypothesis that SBRT is associated with a smaller economic burden for patients and departments compared to CF-EBRT.…”
Section: Resultssupporting
confidence: 50%
“…Results from both studies support the hypothesis that SBRT is associated with a smaller economic burden for patients and departments compared to CF-EBRT. One study estimated the mean cost of SBRT treatment for patients with early-stage prostate cancer to be $22,152 compared to $35,431 for CF-EBRT (33). The other study estimated a mean lifetime cost of $24,873 for patients treated with SBRT compared to $33,068 for CF-EBRT (34).…”
Section: Resultsmentioning
confidence: 99%
“…The disease site most often evaluated in rt costing studies was prostate cancer (39%) 7,9,10,[15][16][17][18]24,27,29,31,32,34 , followed by breast cancer (18%) 8,19,22,25,26,28 , non-smallcell lung cancer (12%) 20,23,37,39 , head-and-neck cancer (9%) 14,33,38 , cervical cancer (6%) 13,21 , and other sites [bone metastases (6%) 12,30 , metastatic epidural spinal cord (3%) 36 , oropharyngeal cancer (3%) 35 , and squamous cell cancer of the anus (3%) 11 ]. Thirteen studies used original costing data to conduct the costing analysis 8,19,20,[24][25][26]28,[29][30][31][32][33]37 ; the remaining twenty studies modelled outcomes using hypothetical patient cohorts 7,…”
Section: Methods In the Included Studiesmentioning
confidence: 99%
“…As shown in Figure 2, twenty-two studies provided costs for imrt 7,[9][10][11]14,[16][17][18][19][20][21][22][23][24]27,28,29,[31][32][33][34][35] ; sixteen, for 3D-c rt 11,14,15,17,19,20,22,23,28,[31][32][33][34][35]37,39 ; six, for bt 9,13,22,24,31,32 ; and six, for sbrt 7,10,20,23,27,37 . A number of studies also costed other modalities of rt (rt in general, whole-breast radiation, external-beam partial-breast irradiation, etc.…”
Section: Methods In the Included Studiesmentioning
confidence: 99%
“…Prior studies have investigated the cost-effectiveness of various prostate cancer treatment modalities. Many of these studies have made comparisons among radiotherapy techniques, including brachytherapy and various radiotherapy techniques such as intensity-modulated radiotherapy (IMRT), stereotactic body radiotherapy (SBRT), and 3D-conformal radiotherapy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Other studies have focused on comparisons among surgical techniques (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%